Resepsi Pembaca Mengenai Omnibus Law di Media Online - Agung Setiadi; Yadi Supriadi (UNISBA Press, 2022)
Abstract. This research is motivated by the phenomenon of changing the law which is currently known as the Omnibus Law. The plan drawn up by the President of Indonesia has drawn many differences of opinion in various levels of society. The law, which is widely known as the universal sweeping law, was successfully ratified through the work copyright law, this was also widely reported by one of the mass media which became a means for the public to consume information, namely, published in the 7th edition of Kompas.com news. October 2020 which explains the series of processes for the ratification of the Omnibus Law. The news describes that the government is still designing and continuing to the stage of ratification regardless of the demands for rejection of articles from the workers who are felt to be able to cut workers' rights. So that this impact gave birth to a public response, especially among students who closely became representatives of the wider community of intellectuals in voicing policies that they felt were not in accordance with the needs of the community. This study aims to determine the reception and hypothetical position of readers regarding Omnibus Law news in online media. The methodology used in this study is qualitative with a Stuart Hall reception analysis approach. The results of this study indicate that news about omnibus law in the online media Kompas.com contains news elements that are informative and provide education according to all informants. Their positions in receiving messages were also different, the eight informants received the message in full, and only one person received the message based on the results of their thinking. Abstrak. Penelitian ini di latar belakangi dengan adanya fenomena perubahan undang – undang yang saat ini dikenal dengan Omnibus Law. Rencana yang disusun oleh Presiden Indonesia tersebut banyak menuai perbedaan pendapat di berbagai lapisan masyarakat. Undang – undang yang banyak dikenal dengan sebutan undang – undang sapu jagat itu berhasil disahkan melalui undang – undang cipta kerja, hal ini juga banyak diberitakan oleh salah satu media massa yang menjadi sarana masyarakat untuk mengkonsumsi informasi yakni, dimuat dalam berita Kompas.com edisi 7 oktober 2020 yang menjelaskan rentetan proses disahkannya Omnibus Law tersebut. Berita tersebut menjabarkan pihak pemeirntah yang tetap merancang dan meneruskan hingga tahap pengesahan tanpa menghiraukan tuntutan penolakan pasal dari kaum buruh yang dirasa bisa memangkas hak pekerja. Sehingga dampak tersebut melahirkan respon masyarakat khususnya dikalangan mahasiswa yang erat menjadi perwakilan masyarakat luas dari kaum intelektual dalam menyuarakan kebijakan yang dirasa tidak sesuai dengan kebutuhan masyarakat. Penelitian ini bertujuan untuk mengetahui resepsi dan posisi hipotekal pembaca mengenai berita Omnibus Law di media online. Metodologi yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan analisis resepsi Stuart Hall. Hasil dari penelitian ini menunjukan bahwa berita mengenai omnibus law dalam media online Kompas.com mengandung unsur berita yang informatif dan memberikan edukasi menurut semua informan. Posisi mereka dalam menerima pesan pun berbeda, kedelapan informan menerima pesan dengan penuh, dan hanya satu orang yang menerima pesan berdasarkan pada hasil pemikirnnya.